1979
DOI: 10.1093/oxfordjournals.aje.a112781
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Influenza Aboard a Commercial Airliner

Abstract: A jet airliner with 54 persons aboard was delayed on the ground for three hours because of engine failure during a takeoff attempt. Most passengers stayed on the airplane during the delay. Within 72 hours, 72 per cent of the passengers became ill with symptoms of cough, fever, fatigue, headache, sore throat and myalgia. One passenger, the apparent index case, was ill on the airplane, and the clinical attack rate among the others varied with the amount of time spent aboard. Virus antigenically similar to A/Texa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
389
0
12

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(407 citation statements)
references
References 5 publications
6
389
0
12
Order By: Relevance
“…Unfortunately, there are very few experimental studies of human-to-human transmission; besides, existing studies are inconclusive and predate the discovery of the influenza virus [32,46,47]. Indirect evidence for influenza transmission between humans can nevertheless be found in observational studies in close contact settings, such as aeroplanes, hospitals, households, schools, and day-care centres [48][49][50][51][52][53]. In particular, influenza transmission is more intense in the household than in the community [51,54], while clinical trials have shown that treating index cases with antivirals reduces secondary transmission to household members [55].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are very few experimental studies of human-to-human transmission; besides, existing studies are inconclusive and predate the discovery of the influenza virus [32,46,47]. Indirect evidence for influenza transmission between humans can nevertheless be found in observational studies in close contact settings, such as aeroplanes, hospitals, households, schools, and day-care centres [48][49][50][51][52][53]. In particular, influenza transmission is more intense in the household than in the community [51,54], while clinical trials have shown that treating index cases with antivirals reduces secondary transmission to household members [55].…”
Section: Discussionmentioning
confidence: 99%
“…Instances where airborne transmission is believed to have contributed to human-to-human spread of influenza arising from time spent in aircraft have been documented [5][6][7]. The outdoor air ventilation rate of the cabin can be a determinant of such outbreaks, as inadequate ventilation prevents effective dilution of airborne droplet nuclei [3][4].…”
Section: Discussionmentioning
confidence: 99%
“…However, their relative importance is likely to vary according to situation, with poor ventilation generally favouring airborne transmission [3]. Furthermore, Moser et al [5] concluded that inadequate ventilation was the main cause of an influenza outbreak (attack rate 72%) when an aircraft was grounded for 3 hours. The conditions during that outbreak were particularly amenable to airborne transmission [3].…”
Section: Figures 1a B and C Show The Relationship Between Trip Duratmentioning
confidence: 99%
“…The duration of influenza outbreaks varies strongly, ranging between a few days [9] and several months [10,12,13], and depends on multiple factors, such as the clientele of patients, the local setting in the hospital, the vaccination rates of HCWs and patients and the introduction of control measures. In this case, the duration of the outbreak was 10 days, suggesting that the introduction of control measures was effective.…”
Section: Discussionmentioning
confidence: 99%